Assessment of the Analgesic Effect of Ethanol Extract of Red Lemongrass Leaves (Cymbopogon nardus) Using a Mouse Model (Mus musculus) - Findi Prasetia; Muhammad Tasjiddin Teheni; Sarni (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Public interest in plant-based traditional medicines continues to increase, encouraging scientific evaluation of commonly used herbal materials, including red lemongrass (Cymbopogon nardus) leaves, which are presumed to possess analgesic properties. Objectives: This study aimed to evaluate the analgesic effectiveness of the ethanol extract of red lemongrass leaves (Cymbopogon nardus) in mice (Mus musculus). Methods: An in vivo experimental design was employed using mice as the test model. Analgesic activity was assessed by quantifying the number of writhing responses (wriggles) following pain induction. The extract was administered in three dose groups, and the data were analyzed using one-way ANOVA to determine differences among groups. Results: The ethanol extract of red lemongrass leaves demonstrated analgesic activity in mice, indicated by a reduction in writhing responses. The highest analgesic effect was observed at a dose of 800 mg/kg body weight, suggesting a dose-dependent relationship in which higher extract doses produced greater analgesic activity. One-way ANOVA showed a significant difference among the extract-treated groups (F = 2.434 > Fcrit = 2.067), leading to rejection of the null hypothesis and confirming statistically significant variation across doses. Conclusion: Ethanol extract of red lemongrass leaves (Cymbopogon nardus) exhibits analgesic effects in mice (Mus musculus), with the most effective dose in this study being 800 mg/kg body weight. The findings support a dose-dependent analgesic response and indicate the potential of C. nardus as a candidate for further analgesic development. Keywords: Cymbopogon nardus; ethanol extract; analgesic activity; writhing test; Mus musculus